(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Stress is the priceless poison for human life in the universe. It can disturb any one’s physical, mental, emotional and behavioral balance. Stress can damage different parts of human body from tissues to organs and blood vessels. It can speed up pulse rate and respiration. It can raise blood pressure and body temperature. It can also interfere with the body metabolism, digestion, appetite, sleep, sexuality and even fertility. There are many problems, which touch the spinning mill sector. In today’s changing and competitive work environment, stress level is increasing both in the workers as well as in the managers. As a result of this work stress, more and more managers are showing signs of chronic fatigue and burnout. Research has concluded that stressed out managers are not managers are not lead to reduced efficiency in even the best of individual, which in turn lead to reduced productivity. Stress is a problem in almost all the countries of the world, irrespective of whether the economy is strong or weak. Therefore, it become very essential to include, “work stress” as one of the chapters in studying human behavior, because we must know what is actually stress, what are the causes of stress, what are its consequences and then, what should be done to reduce it.